The Implication of Digital Organisational Culture on Firm Performance - Pradana, Mahir; Silvianita, Anita; Syarifuddin, Syarifuddin; Renaldi, Renaldi (Frontiers in Psychology, 2022)
Digital technologies have become a major factor for innovation in the business environment. Organisations have taken advantage of digitised data and information to increase performance. However, there is still little research focusing on the effect of digitalisation on organisational culture, which in the end will affect performance. We develop this research by exploring a proposed model involving digital organisational culture with the final goal to enhance organisational performance. The research involved 263 managers of state-owned companies in Indonesia. We analysed the theoretical model by using structural equation modelling and processed the data using the SmartPLS version 3 software. We conclude that digital organisational culture can become an essential factor in improving digital strategy and performance. However, business digitalisation does not really affect digital organisational values.